Processing Student Comments on Understanding of Lecture Materials Using Rule Based Automata Finite State Model - Febri Febri; Suharmanto Suharmanto (International Journal of Information Engineering and Science, 2024)
Serang Raya University, is a private tertiary institution in the province of Banten, There are 4 faculties, Vocational D3 and 17 Study Programs, in the process of teaching and learning activities each lecturer has a different way of teaching students. Faculty of Information Technology, Computer Science Engineering study program with 30 lecturers, 9 classes, 59 courses and 126 students. This does not require the possibility that with the number of courses taken on campus there are sti ll many students who do not understand what the lecturer is delivering. Management of student comments on the understanding of lecture material is designed to make it easy for students to comment on the lecturer's presentation of the material. This is also used as evaluation material for lecturers regarding the delivery of material. Currently, Serang Raya University does not have a website-based information system. From this discussion, comments are made with the Rule-based Finite State Automata model. In reading the comments, this produces a system that can read comments word by word until the end of the word with a space separator so that it finds keywords, namely the keywords understand and don't understand.